On embedding assessments of self-regulated learning into licensure activities in the health professions: a call to action (Canadian Medical Education Journal, 2022)
How well have healthcare professionals and trainees been prepared for the inevitable demands for new learning that will arise in their future? Given the rapidity with which ‘core healthcare knowledge’ changes, medical educators have a responsibility to audit whether trainees have developed the capacity to effectively self-regulate their learning. Trainees who engage in effective self-regulated learning (SRL) skilfully monitor and control their cognition, motivation, behaviour, and environment to adaptively meet demands for new learning. However, medical curricula rarely assess trainees’ capacity to engage in this strategic process. In this position paper, we argue for a paradigm shift toward assessing SRL more deliberately in undergraduate and postgraduate programs, as well as in associated licensing activities. Specifically, we explore evidence supporting an innovative blend of principles from the science on SRL, and on preparation for future learning (PFL) assessments. We propose recommendations for how program designers, curriculum developers, and assessment leads in undergraduate and postgraduate training programs, and in licensing bodies can work together to develop integrated assessments that measure how and how well trainees engage in SRL. Claims about lifelong learning in health professions education have gone unmatched by responsive curricular changes for far too long. Further neglecting these important competencies represents a disservice to medical trainees and a potential risk to the future patients they will care for.